Quick and Sensitive UPLC-ESI-MS/MS Method for Simultaneous Estimation of Sofosbuvir and Its Metabolite in Human Plasma - Semreen, Mohammad H. (Molecules, 2019)
A simple, fast and highly sensitive RP-UPLC-MS/MS method was developed and validated for the simultaneous determination of sofosbuvir (SR) and its metabolite GS331007 in human plasma using ketotifen as an internal standard (IS). The separation was achieved on Acquity UPLC BEH C(18) (50 × 2.1 mm, i.d. 1.7 µm, Waters, USA) column using acetonitrile:5 mM ammonium formate:0.1% formic acid (85:15:0.1% v/v/v) as a mobile phase at a flow rate of 0.35 mL/min in an isocratic elution. The Xevo TQD UPLC-MS/MS was operated under the multiple-reaction monitoring mode using positive electrospray ionization. Extraction with dichloromethane was used in the sample preparation. Method validation was performed as per the Food and Drug Administration (FDA) guidelines and the calibration curves of the proposed method were found to be linear in the range of 1–1000 ng/mL for SR and in the range of 10–1500 ng/mL for its metabolite (GS331007) with an elution time of 1.83 min. All validation parameters were within the acceptable range according to the bioanalytical methods validation guidelines. Furthermore, the obtained results of matrix effects indicate that ion suppression or enhancement from human plasma components was negligible under the optimized conditions. The proposed method can be applied in high-throughput analysis required for pharmacokinetic and bioequivalence studies in human samples.